An Effect Work Motivation, Work Satisfaction, And Work Environment On Employee Performance Of KFC Outlets In Sibolangit-Berastagi Area - Yudha Syahputra; Hendra Utama; Wulan Dayu (Sean Institute, 2024)
This study aims to analyze the influence of work motivation, job satisfaction, and work environment on employee performance at KFC Outlets in the Sibolangit - Berastagi Area, both partially and simultaneously. The study population consisted of 42 employees, all of whom were taken as samples using saturated sampling techniques. Primary data were collected through questionnaires and analyzed quantitatively using multiple linear regression methods with the SPSS version 24.0 application. The results of the analysis indicate that work motivation, job satisfaction, and work environment have a positive and significant influence on employee performance, both partially and simultaneously. Partially, work motivation has a regression value of 0.395, t count (5.098) > t table (2.024), and a significant 0.000 <0.05. Job satisfaction shows a regression value of 0.272, t count (3.040) > t table (2.024), and a significant 0.004 <0.05. The work environment has a regression value of 0.150, tcount (2.694) > ttable (2.024), and a significance of 0.010 < 0.05. The simultaneous test (F test) produces Fcount (168.652) > Ftable (2.852) with a significance of 0.000 < 0.05, so that the hypotheses H1, H2, H3, and H4 are accepted. The work motivation variable was found to be the dominant factor with the highest regression value. The determination test shows that 92.5% of employee performance is influenced by work motivation, job satisfaction, and work environment, while 7.5% is influenced by other factors. The relationship between employee performance and these three variables is very strong.